HUBUNGAN PERILAKU ADIKSI MEDIA SOSIAL (TIKTOK) TERHADAP HASIL BELAJAR AKIDAH AKHLAK SISWA KELAS X MADRASAH ALIYAH AL-ISLAM JAMSAREN SURAKARTA TAHUN PELAJARAN 2025/2026 - Salsabila, Nafiisa Saniya; Mujiburrohaman, Mujiburrohaman (STKIP Pesisir Selatan, 2025)
This study examines the relationship between TikTok social media addiction behavior and learning outcomes in Akidah Akhlak (Islamic theology and morality) among Grade X students at MA Al-Islam Jamsaren, Surakarta, in the 2025/2026 academic year. The research is motivated by widespread TikTok use among adolescents, which is suspected to distract from learning, especially in subjects aiming to instill religious values. A quantitative correlational design was employed with a total sampling of 66 students (the entire Grade X). TikTok addictive behavior was measured via a closed-ended questionnaire (30 items, 4-point scale), while Akidah Akhlak learning outcomes were taken from mid-semester test scores. Pearson’s correlation test was used for analysis. The results show that students’ TikTok addiction levels were moderate to high (mean score 91.09 on a 30–120 scale; 73% of students in moderate or high category), whereas their Akidah Akhlak outcomes were generally moderate tending to low (mean = 81.58 on a 0–100 scale; 68% in moderate or low category). Normality and homogeneity tests indicated the data met assumptions (p>0.05). The Pearson correlation coefficient was r = 0.144 with p = 0.247, indicating no significant relationship between TikTok addictive behavior and Akidah Akhlak learning outcomes.